2013
DOI: 10.1111/are.12362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varied levels of incorporation ofLabeo goniusin carp polyculture system in India

Abstract: Growth performance of kuria labeo, Labeo gonius as a component species in the major carp polyculture system was evaluated at two incorporation levels against a control without the species through a year‐round grow‐out study in nine earthen ponds (0.08 ha). Three species ratio of catla, silver carp, rohu, mrigal and kuria labeo at 15:15:40:30:0 (T‐1: control), 15:15:40:20:10 (T‐2) and 15:15:40:10:20 (T‐3) were evaluated as three treatments. The carps were stocked at a combined density of 7500 fingerlings ha−1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…This may be due to the hardier nature of L. gonius, which is adapted to bottom-dwelling habitats. These ndings align with previous studies on sh co-culture Jena et al, 2015). In comparison to the present study, reported the dominance of L. gonius over L. rohita in terms of both growth and survival in their rearing with L. mbriatus and Puntius gonionotus.…”
Section: Fish Growth and Survivalsupporting
confidence: 93%
“…This may be due to the hardier nature of L. gonius, which is adapted to bottom-dwelling habitats. These ndings align with previous studies on sh co-culture Jena et al, 2015). In comparison to the present study, reported the dominance of L. gonius over L. rohita in terms of both growth and survival in their rearing with L. mbriatus and Puntius gonionotus.…”
Section: Fish Growth and Survivalsupporting
confidence: 93%
“…They were stocked with 350 fish in total, resulting in a stocking density of 14,414 fish per hectare (Ayyappan and Jena, 2003). The ponds were fertilized by following the standard protocol (Jena and Das, 2006). The fishes were fed ad libitum with roughly 3% of their weight twice a day for five months.…”
Section: Fish Husbandry and Feeding Trialmentioning
confidence: 99%